The Influence Of Auditor Reputation, Firm Size, And Underwriter's Reputation On Share Underpricing - Putri Novia Rini; Prisila Damayanty (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to examine the effect of auditor reputation, firm size, and underwriter reputation on stock underpricing. The population used in this study were companies that conducted an Initial Public Offering (IPO) on the Indonesia Stock Exchange (IDX) for the period 2018 – 2021. The sample in this study was 124 companies using a purposive sampling method. The data analysis method in this study used multiple linear regression analysis with SPSS Version 26. The results showed that auditor reputation had a significant negative effect on stock underpricing, while firm size and underwriter reputation had a significant positive effect on stock underpricing and auditor reputation, firm size, and underwriter reputation simultaneously had a significant positive effect on stock underpricing Keywords: Auditor Reputation, Firm Size, Underwriter Reputation, Stock Underpricing